Territorial Capital And The Great Recession: A Nuts-3 Analysis For Southern Italy - Fabio Mazzola; Rosalia Epifanio; Iolanda Lo Cascio; Giuseppe Di Giacomo (European Regional Science Association (ERSA), 2012)
Up to now, the analyses of the current "Great Recession" have been mainly confined to the national and international scale leaving aside the differential effects of the crisis upon regions and smaller areas. Although the current crisis has a strong international and global flavor, it must be admitted that the different structural characteristics of regions and urban areas might be often responsible for the specific economic and social impact of the recession and will strongly determine the possibility of resilience in the future. In the effort of better defining which regional characteristics may be considered as strategic for measuring the absorption capacity of the region vis-à-vis the great recession, in this paper we focus on territorial capital, a broader concept of capital which takes into account different characteristics of goods and services according to the degree of appropriability and rivalry (public or private) and the material or non-material physical content (Camagni, 2008). By making use of a large data set on southern Italian provinces which mostly focus on soft indicators of regional endowments, we try to measure the empirical relationship between territorial capital and the change in income per capita and employment. As a matter of fact, most "hybrid" elements of territorial capital (relationships between firms, cooperation networks, public-private partnership, governance of the territory, activity in the intermediation of innovation and so on) assume specific relevance in the building of territorial capital endowment of less developed and peripheral regions and may have been caused a different reaction at the regional or subregional level. Conversely, we also want to investigate the causality direction: in other words we ask ourselves if the territorial capital endowment enhances economic development or if the local economic performances contribute to capital accumulation and, furthermore, if the direction changes before and after the crisis. The interactive and cumulative nature of territorial capital accumulation generates differences that change only at very slow pace. This might influence not only the economic development of the unit of analysis but also the velocity of convergence at a provincial scale.
Keywords: 330